On-chip bi-semicircular slot antenna at 550 GHz for 2×4 coherent source array in 65nm CMOS technology - Hsin-Chia Lu; Hong-Pei Chen; Yan Zhao; Chang, Mau-Chung Frank (Digest - IEEE Antennas and Propagation Society. International Symposium (1995), 2015)
This paper presents the design and measurement results of on-chip differential fed semi-circular slot antenna. Slot antenna allows easy metal density adjustment to comply with design rule requirement on standard CMOS process. This antenna works with a triple-pushed Colpitts voltage control oscillator (TPCVCO) to form a monolithically integrated 2×4 coherent source array operating at 0.54-0.55 Tera-Hertz (THz) in 65nm digital CMOS technology. The source array is tested to radiate 61 and 126 uW THz power by consuming 0.5 and 1.3W DC power, respectively. According to measured antenna directivity of 36.4dBi and simulated radiation efficiency of 50%, source array's equivalent isotropic radiated power (EIRP) is estimated to be 21.2 and 24.4 dBm, respectively. To the best of our knowledge, this is the 1 st coherent THz source made of monolithically integrated silicon IC technology beyond 0.5 THz.